Teoria crítica feminista e crítica à(s) criminologia(s) estudo para uma perspectiva feminista em criminologia no Brasil - Campos, Carmen Hein de (2013)
Critical criminology and feminism in Brazil have, in the struggle for human rights and democratization of the country, from the sixties, their common root. Paradoxically, this political proximity has not resulted into an academic approach, despite the fruitful scientific developement made by both critical criminology and feminist theory. The resistance of criminology to include gender as a new theoretical paradigm, which would allow the second criminological turn gender turn (beside to the labeling approach), makes critical criminology antifeminist. This finding in Brazil raises questions about possibility of a feminist criminology. In turn, the new subjects of feminism women slum, black, lesbians whose specific vulnerabilities also determine specific violence require inclusion and recognition. Development of a feminist criminology claims to incorporate gender to the malestream, and the inclusion of new subjects of feminism, ie, populations historically erased from the view of both feminism and criminology, providing a multi-dimensional perspective and a new aesthetic for a feminist perspective in criminology in Brazil.